SHOTGUN INJURY AS A CAUSE OF FLOATING ELBOW: A CASE REPORT - Stojiljkovic, Predrag Miroslav; MIlutinovic, MIljana; Krstić, Andrija; Ciric, Tamara; Mladenovic, Marko; Stojiljkovic, Aleksandra (Acta medicae Medianae, 2024)
Floating elbow represents an injury that is a combination of ipsilateral humeral shaft and forearm fractures. Shotgun injury of the elbow is a very severe and complex type of injury, often with complications such as infection, nerve palsy, and range of motion limitation. We present a case report of a 46-year-old man with a gunshot wound to the right elbow. He sustained an injury of the distal humerus and proximal ulna which resulted in a floating elbow injury. As the initial clinical exam indicated normal neurovascular status, after adequate preoperative preparation, primary surgical treatment of the wound was performed under general endotracheal anesthesia as well as stabilisation of the right elbow with the Mitković external fixator with two pins placed in the humeral shaft and two pins placed in ulna shaft. Two weeks later we performed internal fixation of the mentioned injury. Surgical treatment of such severe gunshot wounds requires primary treatment with an external fixator with subsequent conversion to internal fixation when the local status of the wound is normal. Floating elbow injuries should be brought into the correct anatomical reposition as soon as possible with internal fixation because it allows us to have good function of the elbow with the best possible range of motion.